Rockburst mechanism in coal rock with structural surface and the microseismic (MS) and electromagnetic radiation (EMR) response. (June 2021) - Li, Xuelong; Chen, Shaojie; Wang, Enyuan; Li, Zhonghui
Highlights: We established the elastic-plastic-brittle mutation rockburst model of coal rock with structural surface. We established the volume element-region-system model of rockburst. We researched on the relationship between energy accumulation and dissipation during the coal rock dynamic rupture process. Abstract: Rockburst is a complex coal and rock dynamic disaster, which poses a serious threat to safe and efficient mining activities. With the increase in the mining depth and strength, rockburst becomes more and more serious. Coal rock contains different types and sizes of structural surface, and its bucking failure is the result of crack propagation and coalescence. In this paper, based on the elastic–plastic mechanics and damage mechanics, we established the elastic–plastic-brittle mutation rockburst model of coal rock with structural surface, introduced the concept of the coal rock volume energy potential function, and researched the relationship between energy accumulation and dissipation during the coal rock dynamic deformation and rupture process to obtain the rockburst energy condition. In addition, the volume element-region-system model of rockburst was established to explain the rockburst evolution process very well. In the external disturbance or high stress state, the coal rock system volume element is destroyed and quickly releases energy to the adjacent volume element. When the adjacent volume element cannot absorb this energy, it is destroyed, and the energy is released quickly. This energy release forms a chain reaction, and the local coal rock is unstable. Eventually, the entire coal rock system is unstable, and rockburst happens. Based on the above theory, the microseismic (MS) and electromagnetic radiation (EMR) characteristics of coal rock in the rockburst evolution process were analyzed. The significance of the study lies in both theory and practice for deeply understanding the rockburst mechanism, as well as for accurate monitoring and early warning.